Effects of User-Induced Transients on a Service Line: Preliminary Results from WEL (Perugia, Italy) - Valentina Marsili; Debora Falocci; Caterina Capponi; Silvia Meniconi; Filippo Mazzoni; Stefano Alvisi; Bruno Brunone; Marco Franchini (Engineering proceedings, 2024)
The integrity of water service lines (SLs), crucial components in water distribution networks, is potentially threatened by transients generated by users’ activity. This paper presents the results of laboratory tests carried out at the Water Engineering Laboratory of the University of Perugia (Italy) to investigate the effects of user behavior on an SL. In particular, transients due to changes in the discharge in the SL, simulating the activation of domestic devices, are investigated. The analysis of the effect of such maneuvers provides insights that can assist water utility managers in the design, installation and maintenance of SLs.